AI-Assisted Reference Data Harmonization Across Global Data Center Systems - Sreenivasulu Naidu Yalakaturi (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Formal and independent evidence lays bare the complexity ofReference Data, distinguished from Master Data, Dimensional Data and Metadata. While harmonization aligns disparate Data Sources within andbetween Organizations, Data Native to one Organization becomes the Standardagainst which Data from others is Normalized. Sovereignty, Privacy, Regulatory and Risk Management Policies therefore inform the Architecture of AI-AssistedHarmonization Workflows and the Design of Harmonized Data Repositories.